Editorial - Fraga, Maria de Nazaré de Oliveira (Rev Rene, 2004)
The results of some important advances in the health field boosted the survival of the population, as preventive measures and vaccines, for example. Such measures, while there were, allowed many lives to be stopped early. Also as a result of these advances, the precocity and expansion of diagnostic processes of certain health disorders that previously remained unknown or without concrete possibilities for specialized care also contributed to the important part of survival of the human population.